Exploratory and factorial analysis of the ‘Questionnaire of psychosocial factors at work’ in Peru - Pando Moreno, Manuel (2016)
Introduction. The evaluation of negative psychosocial factors or psychosocial risk factors is a lengthy process, but the majority of methods rely on the use of an instrument or scale, of which we find a wide diversity. However, few have been designed and validated to be applied in Latin America. Objective. To validate an instrument of evaluation of psychosocial factors for its application in workers in Peru. Design. Exploratory factorial analysis of the Questionnaire of Psychosocial Factors at Work with a population of Peruvian workers. Participants. Lima, Arequipa and Trujillo workers. The population consisted in 542 subjects working in construction, textile industry, education services, health, mining, fisheries and agroindustry among others. The statistical analysis was based on the determination of the Cronbach’s alpha coefficient, percentage of variance explained and the eigenvalues of each item of the scale. Results. The Cronbach α coefficient of the questionnaire in general was 0.9, indicating excellent reliability, being above the results of other similar scales. Individually most of the 7 factors of the questionnaire obtained satisfactory values. Those that presented Cronbach’s alpha below 0.7 were ‘Workload’ α = .5, that would qualify as ‘Inadequate’ and ‘Content and characteristics of the task’ with α = .6, qualifying as ‘Adequate but with deficits’. Conclusions. It is possible to use the ‘Questionnaire of Psychosocial Factors at Work’ for the purposes of research and evaluation in companies in Peru.